ANALYSIS OF LEADERSHIP STYLE IN IMPROVING THE PERFORMANCE OF STATE CIVIL APPARATUS (ASN) OF BUKIT BESTARI DISTRICT: Analisis Gaya Kepemimpinan dalam Meningkatkan Kinerja Aparatur Sipil Negara (ASN) Kecamatan Bukit Bestari - Yunita, Echa; Wardani, Novy Eka; Cahyani, Sheila Indah; Satriadi, Satriadi (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The performance of the State Civil Apparatus (ASN) in the sub-district is greatly influenced by the leadership style applied. Bukit Bestari District faces various challenges in improving the performance of the State Civil Apparatus, such as limited resources, low discipline, and lack of effective communication between leaders and subordinates. This study aims to analyze the leadership style applied in Bukit Bestari District and its impact on improving the performance of the State Civil Apparatus. The research method used was qualitative descriptive, with data collection through interviews with section heads and sub-district employees. The results of the study show that participatory leadership is the dominant model applied, where leaders try to involve employees in decision-making and encourage open communication. This leadership style has an impact on improving the performance of the State Civil Apparatus, although there are still challenges in its implementation. So it can be concluded that effective leadership can improve the performance of the State Civil Apparatus by means of more intensive communication, a transparent reward system, and periodic training. Therefore, a more adaptive strategy is needed in managing the State Civil Apparatus to improve its performance in Bukit Bestari District